1999
DOI: 10.1074/jbc.274.9.5415
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization and Scaffolding Functions of the Erythropoietin Receptor Cytoplasmic Tail

Abstract: Signal transduction by the erythropoietin receptor (EPOR) is activated by ligand-mediated receptor homodimerization. However, the relationship between extracellular and intracellular domain oligomerization remains poorly understood. To assess the requirements for dimerization of receptor cytoplasmic sequences for signaling, we overexpressed mutant EPORs in combination with wild-type (WT) EPOR to drive formation of heterodimeric (i.e. WT-mutant) receptor complexes. Dimerization of the membrane-proximal portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
(48 reference statements)
1
33
0
Order By: Relevance
“…Moreover, it is known that mutation of a tryptophan residue in the interbox1\box2 region of the EPOR also abrogated signal transduction, although binding to Jak2 was maintained [12,27] or, conversely, could not be detected [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is known that mutation of a tryptophan residue in the interbox1\box2 region of the EPOR also abrogated signal transduction, although binding to Jak2 was maintained [12,27] or, conversely, could not be detected [29].…”
Section: Discussionmentioning
confidence: 99%
“…In such a receptor complex, both chains associate with Jaks, which is a prerequisite for signal transduction to occur [18,27]. However, only the wild-type cytoplasmic part of gp130 sustains Jak activation.…”
Section: Jak Association To Both Chains Of a Gp130 Dimer Is Essentialmentioning
confidence: 99%
“…Structural and biochemical analyses have demonstrated that epo induces receptor dimerization (Barber et al, 1994;Livnah et al, 1996;Matthews et al, 1996;Watowich et al, 1992Watowich et al, , 1994. The dominant action of mutant receptors in J2E cells suggests that they heterodimerize with wild type receptors upon ligand binding, thereby altering normal receptor function.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant epo receptors D257 (Watowich et al, 1994), D321 (Watowich et al, 1999) and W282R , together with wild type epo receptor tagged at the carboxy terminus with HA (wt-HA), were subcloned into the retroviral vector MSCV 2.2 (Hawley et al, 1994). Plasmids were transfected into PA317 amphotropic packaging cells and virus-containing supernatants added to J2E or J2E-NR cultures before selection in Geneticin (Sigma, St. Louis, MO, USA) as described previously .…”
Section: Transfection Of Epo Receptorsmentioning
confidence: 99%
See 1 more Smart Citation